Persons with physical disabilities' experiences of rehabilitation services at Community Health Centres in Cape Town. - C.K. Kahonde; N. Mlenzana; A. Rhoda (AOSIS, 2010)
Background: Rehabilitation is of fundamental importance for the persons with disability to achieve functional independence and have an improved quality of life. To enhance the effectiveness of rehabilitation, it  is  important  to  seek  clients'  perspectives  of  the  rehabilitation  services and  to  incorporate  these  perspectives  into  the  planning  and  delivery  of rehabilitation  services.  The  aim  of  this  study  was  to  explore  the  persons with  physical  disabilities'  experiences  of  the  rehabilitation  services  they received at Community Health Centres (CHCs). Methods: In-depth  qualitative  interviews  were  used  to  collect  data.  Ten  persons  with  physical  disabilities,  who  had  received  rehabilitation  services at CHCs participated in the in-depth interviews. The interviews were tape-recorded and transcribed verbatim.  Thematic analysis was used to analyse the data.  Results: The  clients  experienced  problems  with  accessing  transport  and  obtaining  information  from  the  service providers. Experiences regarding clients' involvement in the rehabilitation were varied. All the clients reported positive experiences regarding their interaction with service providers and family involvement. Conclusion: The experiences of the participants who accessed CHCs for rehabilitation were positive and negative. The service providers should therefore address the aspects of rehabilitation that were negatively experienced.